Anatomic pathological aspects of canine transmissible venereal tumor - Calderon, C.; Oliveira, R. R.; Marquez, E. S.; Cruz, M. F. R. (Scientific Electronic Archives, 2016)
Canine transmissible venereal tumor, TVT, is a very common aggressive neoplasm, and the most affected animals are dogs, and other canids may also be affected. There are many forms of transmission, and this naturally occurs between the carriers, sexual intercourse is considered a major route of transmission, it is usually found in urban areas with an environment with a large population of free-roaming dogs and affect dogs and bitches. The TVT can clinically appear macroscopic form with lumps of various sizes, ulcerated, necrotic or not, and its development is usually in the genitals with associated secondary problems, such as urinary retention and others. The tumor diagnosis, in addition to anamnesis should be associated with the cytological or histological analysis. Several techniques are used to collect samples for analysis in microscopy, where the best technique to be used in the diagnosis of TVT is the aspiration cytology. The chemotherapy is considered the most effective method for TVT treatment, and vincristine sulfate is the drug of choice.